Perancangan Interior Café Edukasi dan tempat Wisata Di Surabaya - Christa Bella Hartawati; Andereas Pandu Setiawan (Intra, 2016)
Increasingly tight schedule of community activities make urban society requires a have easy access to visit and have a facility sufficient to relax with the family, school friends, lectures and colleagues. Many down-town city big had a meal that provides facilities for a place to gather and relax. Unfortunately places entertainment does not contain elements of education and only limited places of entertainment only. Schedule urban society so dense and full of activities also made their forget their surroundings and seem more individual. Yet as we know, the environment is very important to the survival of humans and ecosystems. Therefore creates a gathering place that is café that also provide educational facilities of green plants to urban communities, especially in the city of Surabaya.